2012
DOI: 10.3198/jpr2011.11.0605crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Ho 02‐113’ Sugarcane

Abstract: PI 665695) sugarcane (a complex hybrid of S. officinarum L., S. spontaneum L., S. barberi Jeswiet, and S. sinese Roxb. Amend. Jeswiet) was released by the USDA-ARS Sugarcane Research Unit working cooperatively with the Louisiana State University Agricultural Center and the American Sugarcane League of the USA. This high-fiber sugarcane cultivar was released for use as a biofuel feedstock to fill the rising industry demand. Ho 02-113 is a progeny of the cross SES 234 × 'LCP 85-384' made in Houma, LA in 2001. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…In this study, we demonstrated for the first time that the cpDNA of S. spontaneum was maternally inherited. The three F 1 progeny of S. spontaneum, namely, Ho 02-113 (Pan et al, 2006;Hale et al, 2012), US 99-44, and US 99-47 (Pan et al, 2004a), shared identical cpDNA sequences to those of their maternal S. spontaneum parents, namely, SES 234 and Djatiroto.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, we demonstrated for the first time that the cpDNA of S. spontaneum was maternally inherited. The three F 1 progeny of S. spontaneum, namely, Ho 02-113 (Pan et al, 2006;Hale et al, 2012), US 99-44, and US 99-47 (Pan et al, 2004a), shared identical cpDNA sequences to those of their maternal S. spontaneum parents, namely, SES 234 and Djatiroto.…”
Section: Discussionmentioning
confidence: 95%
“…Several new lines of Saccharum hybrids with an S. spontaneum cytoplasm were selected for further improvement (Pan et al, 2004b(Pan et al, , 2006. One hybrid, Ho 02-113, has been thoroughly tested and released as the first biofuel cultivar that contains the cytoplasm of SES 234, an S. spontaneum clone (Hale et al, 2012). Asano et al (2004) and Calsa et al (2004) published the complete chloroplast genomic DNA sequences of two sugarcane cultivars, namely, NCo 310 (GenBank ID: NC006084) and SP 80-3280 (GenBank ID: NC005878).…”
Section: Introductionmentioning
confidence: 99%
“…The sugarcane cultivar BUFCP 74 1010^was released in Florida as a cellulosic biomass cultivar with resistance to smut as well as to other diseases [82]. The USDA-ARS Sugarcane Research Unit in Houma, LA, in collaboration with Louisiana State University Agricultural Center, and the American Sugarcane League of the USA, Inc. released the high-fiber sugarcane cultivar BHo 02-113^for use as a biofuel feedstock [37]. Ho 02-113 averaged 43.5 Mg/ha DM which was significantly greater than L79-1002 (37.4 Mg/ha DM) and was resistant to leaf scald (Xanthomonas albilineans (Ashby) Dawson), smut, and brown rust (Puccinia melanocephela).…”
Section: Sugarcane/energycanementioning
confidence: 99%
“…The geneticists and breeders then screen the resulting seedlings by cultivar-specific SSR fingerprints to identify true F 1 hybrids for field evaluation and selection and discard self-progeny and off-type progeny derived from stray pollens of unknown source [15]. Within 12 years, the USDA-ARS sugarcane geneticists and breeders were able to release the first energy cane cultivar Ho 02-113 [13] that contains a cytoplasm of SES234, a S. spontaneum clone.…”
mentioning
confidence: 99%
“…Firstly, the geneticists and breeders are able to include molecular descriptors to registration articles on both sugarcane and energy cane (*) cultivars; for example, HoCP 96-540 [8], Ho 95-988 [9], Ho 00-950 [10], HoCP 91-552* [11], Ho 00-961* [12], and Ho 02-113* [13] were all registered with a molecular descriptor.…”
mentioning
confidence: 99%